58 Criminal justice outcomes for high-risk assault-injured youth seeking emergency department care. (19th September 2017) - Dora-Laskey, Aaron; Carter, Patrick; Cunningham, Rebecca
Abstract : Statement of purpose: To describe rates and characteristics of criminal arrests in a sample of drug-using, violently injured youth during the 36 months surrounding an emergency department (ED) visit. Methods/approach: Participants (ages 14–24) screening positive for past six-month drug use and presenting for an assault (AIG) or as part of a proportionally sampled comparison group (CG) of non-assaulted youth were enrolled in a 2 year longitudinal study (n=599). Computerised surveys were administered at baseline, and at 6, 12, 18, and 24 months. Objective arrest data were obtained from law enforcement sources for those >18. Arrest rates were characterised with survival analysis; baseline characteristics predictive of arrest were determined using multivariate Poisson regression. Results: The sample was 59% male and 65% African-American, with a mean age of 20. AIG participants had a 30% greater risk of arrest than the CG (47.2% vs. 36.3%, p<0.05), with 70% of arrests occurring during the 24 month follow-up. The AIG had a higher mean number of arrests (2.23 vs. 1.72, p<0.01). Overall, 40.9% of arrests involved a violent/weapon related crime, 27.9% were property crimes, and 23.2% were related to alcohol or drugs. Where cases resulted in a criminal charge, 50.3% involved fines or restitution, 36.9% involved jail or prison time, and 29.4% involved probation. Regression identified that age (RR=1.04), male sex (RR=1.90), African-American race (RR=1.25), diagnosis of drug use disorder (RR=1.25), and assault-related injury (RR=1.31) increased the risk for criminal arrest. Extra-curricular school and community involvement were found to be protective (RR=0.78). Conclusions: Drug-using youth with assault injuries who seek emergency care have high rates of subsequent criminal arrest. Significance and Contributions to Injury and Violence Prevention Science: The emergency visit for assault injury may be an opportunity to engage youth in services and Interventions that decrease subsequent risk for criminal justice involvement and its negative sequelae.